S=-6z+9z-7z

Simple and best practice solution for S=-6z+9z-7z equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for S=-6z+9z-7z equation:


Simplifying
S = -6z + 9z + -7z

Combine like terms: -6z + 9z = 3z
S = 3z + -7z

Combine like terms: 3z + -7z = -4z
S = -4z

Solving
S = -4z

Solving for variable 'S'.

Move all terms containing S to the left, all other terms to the right.

Simplifying
S = -4z

See similar equations:

| 50*p=30 | | Q=-5y+4y | | Z^4+6z^2+25=0 | | 20n=8 | | 700+0.15x=750 | | 7V+2B=164 | | K=-5c-8c | | -4(3x-1)+2=-12x+6 | | 6y-14=26 | | 2x(8+5squared)= | | 10-5x=6+3x | | .4x-1.9=.5 | | 15+x=40 | | 4n-2a=9 | | 3x/4×2x/4 | | f(x)=3x/5x-25 | | x+7=3(2x-1) | | 4x+3=7x-1.5 | | 6-3p=1 | | 63/3x=21 | | -1x+3x=-3+17x | | 4x+x=3x+1 | | AB+BC=BCD | | 180n^2-360n-2160=0 | | y=0.13+0.4*100 | | 16x-6=16x-6 | | 2x^2+4y^2-2z^2-5y=0 | | Cot(-t)/csc(-t)=cos(t) | | x+2y-3z=-5 | | 6x-1+5y=0 | | 42-(4b/12)=30 | | 6-2(3n+1)=40 |

Equations solver categories